1989
DOI: 10.1007/bf00003468
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of brown algal polyphenols as inhibitors of α-amylase, lipase and trypsin

Abstract: Extracts of Ascophyllum nodosum, Fucus serratus, F. vesiculosus and Pelvetia canaliculata contain inhibitorsof a-amylase, lipase and trypsin. The inhibitors were isolated and identified by 'H NMR spectroscopy as polyphenols which have apparent molecular weights in the range from 30000 to 100 000 daltons, as determined by ultra-filtration with Amicon membranes. These polyphenols account for the whole of the inhibitory activity in crude algal extracts. The compounds inhibit a-amylase and trypsin in an apparently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 5 publications
1
23
0
Order By: Relevance
“…Our results confirmed what was reported by other authors who found that green, red, and brown algae exhibited inhibitor activities against lipases [23,24]. However, it is very important to note that variations in the inhibitory capacities of algal extracts could be related to many factors (the species, the biological stage, environmental conditions, the extraction processing conditions, etc.).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results confirmed what was reported by other authors who found that green, red, and brown algae exhibited inhibitor activities against lipases [23,24]. However, it is very important to note that variations in the inhibitory capacities of algal extracts could be related to many factors (the species, the biological stage, environmental conditions, the extraction processing conditions, etc.).…”
Section: Discussionsupporting
confidence: 92%
“…In addition, it has been shown in vitro that some condensed polyphenols, such as tannin, had an inhibitory action on different digestive enzymes such as proteases, alfa-amylase, and pancreatic lipase [24]. Our findings suggested that C. prolifera may prove to be a good source of effective crude drug for the treatment of obesity.…”
Section: Discussionmentioning
confidence: 55%
“…Phlorotannins are produced by polymerization of phloroglucinol and are known only from brown algae; in addition to UV protection, they have a role in discouraging grazing (135) and inhibit enzyme activity and potentially digestion (7). Tannins present in vascular plants (102) have similar properties, and their occurrence in vascular plants correlates with expanded numbers of mammalian grazers (105).…”
Section: Streptophytinamentioning
confidence: 99%
“…Polyphenolic content in solvent extract of A. nodosum was 82% of the total of untreated A. nodosum (data not shown), resulting in a further 5% being removed during enzymatic saccharification. Seaweeds with high polyphenolic content, such as members of the Fucales, have shown to inhibit microbial processes [67] largely due to the non-selective inactivation of enzymes [68]. Polyphenolics are also known to exhibit an affinity towards proteins but the effect of complex formation on the digestibility of proteins/phenolics and the activity of enzymes is still not fully understood [69] and both beneficial and detrimental effects of polyphenols on digestive enzymes have been reported [70].…”
Section: Polyphenol Contentmentioning
confidence: 99%